Republic of Lithuania : Request for Stand-By Arrangement. (IMF Staff Country Reports; Country Report, 2001)
Lithuania achieved significant progress in macroeconomic stabilization and structural reforms, under the previous Stand-By Arrangement. Executive Directors welcomed the new program, which aimed at maintaining macroeconomic stability, promoting private sector activity, and strengthening external viability in order to attain sustainable growth and create employment opportunities. They stressed the need to implement fiscal and structural reforms. They agreed that the authorities are following an appropriate approach of preparing a medium-term fiscal framework, determining priorities, and seeking ways to achieve the medium-term goal of a balanced budget.